Conceptual mobility model of vertical handover decision in heterogeneous networks - Norakmar Arbain; Zolidah Kasiran (Institute of Advanced Engineering and Science, 2019)
In heterogeneous network, maintaining seamless connectivity needs excessive efforts from various aspects such as network availability and mobile node reliability. Presently, a vertical handover management is a practical approach in facilitating the service continuity for mobile users. Many researches have been conducted in this area by considering performance improvement in delay, latency, and overhead. Preserving the Quality of Services (QoS) based on user mobility and pattern movement during handover decision has become an important aspect in vertical handover management. This paper presents the conceptual mobility model of vertical handover decision in heterogeneous network. Hence, several researches in vertical handover decision management has been reviewed regarding the issues on the vertical handover decision algorithms such as RSS Based Algorithm, MADM Based Algorithm and Intelligence Based Algorithm. This paper highlights the current decision algorithms that integrate the traditional methods with intelligence algorithm for better optimization. In decision parameters, the user mobility pattern can be importance in terms of direction randomness and mobility speed. Hence, a conceptual mobility-awareness model for vertical handover are been proposed in targeting some improvement of handover performance.